Evaluasi Mutu Kimia dan Organoleptik Mi Kering Bebas Gluten dari Tepung Komposit Jagung-Singkong selama Penyimpanan - Rima Kumalasari; Dewi Desnilasari; Sharren Pratama Wadhesnoeriba (Institut Pertanian Bogor, 2018)
Noodles are the staple foods for some countries in the world. Generally, noodles are made from whole wheat or flour from other grains and cereals. Development of noodles from non-wheat flour or gluten-free noodles has been conducted. One type of noodles that is often used is dry noodle. Research on gluten-free dried noodles made from maize and cassava composite flours has been done. The stability of product quality is very important to be studied, especially for designing product storage conditions. This study aims to evaluate the quality of maize-cassava dry noodle products during storage and to obtain the recommended storage temperature of dry maize-cassava noodles. The product is stored at four temperatures, i.e, 8, 28, 38, and 48°C. The temperature at 8°C was used as the control temperature. The products were stored for 8 weeks and the stability of quality parameters (moisture content, free fatty acid, and organoleptic including color, flavor, and taste) of the products were observed weekly. The result showed that there was a change of quality of dried maize-cassava noodle for 8 weeks of storage. Dry maize-cassava noodle had increased free fatty acids (0.029-0.038%), decreased moisture content (0.05-0.23%), and panelist acceptance levels of color, flavor, and aroma. Differences in storage temperature had no significant effect on free fatty acid change, sensory values of color, taste, and aroma, but had a significant effect on the decreased water content. The range of temperature recommendedfor storage of dried noodles of corn-cassava was 28-38°C.